Choosing the Playing Field: Non-Participation in the Village Level Participatory Deliberative Forums - Sambodho, Johanes Prio (UI Scholars Hub, 2019)
This article will address these key questions: why do the poor villagers are not participating within these formal participatory deliberative forums? and what do they do instead in claiming accountability and gain access to services and their everyday livelihood resources? Based on 10 months of village level ethnographic study in a West Java village between 2014 to 2015, this article will focus on how these village level democratic reforms are perceived and experienced by Indonesian villagers, especially by the poor, as they interact with a plethora of village level participatory democratic institutions that are become available. This article argues that despite the proliferation of village level democratic avenues, the poor villagers still regularly rely on informal means in engaging with their elites while at the same time forgo their chances to participate through the formal avenue of participation. These informal practices stem from three key rationales: the differential capacity of the poor to engage within formal deliberative mechanism; preserving their relation with their fellow elites; and increasingly competitive elites that become increasingly accountable in providing them with better access to services.